Bioacoustic Field Research: A Primer to Acoustic Analyses and Playback Experiments With Primates. Issue 7 (16th April 2013) - FISCHER, JULIA; NOSER, RAHEL; HAMMERSCHMIDT, KURT; Higham, James P.; Semple, Stuart
Abstract Acoustic analyses of primate vocalizations as well as playback experiments are staple methods in primatology. Acoustic analyses have been used to investigate the influence of factors such as individuality, context, sex, age, and size on variation in calls. More recent studies have expanded our knowledge on the effects of phylogenetic relatedness and the structure of primate vocal repertoires in general. Complementary playback experiments allow direct testing of hypotheses regarding the attribution of meaning to calls, the cognitive mechanisms underpinning responses, and/or the adaptive value of primate behavior. After briefly touching on the historical background of this field of research, we first provide an introduction to recording primate vocalizations and discuss different approaches to describe primate calls in terms of their temporal and spectral properties. Second, we present a tutorial regarding the preparation, execution, and interpretation of field playback experiments, including a review of studies that have used such approaches to investigate the responses to acoustic variation in calls including the integration of contextual and acoustic information, recognition of kin and social relationships, and social knowledge. Based on the review of the literature and our own experience, we make a number of recommendations regarding the most common problems and pitfalls. The power of acoustic analyses typically hinges on the quality of the recordings and the number of individuals represented in the sample. Playback experiments require profound knowledge of the natural behavior of the animals for solid interpretation; experiments should be conducted sparingly, to avoid habituation of the subjects to the occurrence of the calls; experimenter‐blind designs chosen whenever possible; and researchers should brace themselves for long periods of waiting times until the appropriate moments to do the experiment arise. If all these aspects are considered, acoustic analyses and field playback experiments provide unique insights into primate communication and cognition. Am. J. Primatol. 75:643–663, 2013. © 2013 Wiley Periodicals, Inc.